Armenia : Child Welfare Note - World Bank (Washington, DC, 2013)
This Note was prepared in response to the needs for technical assistance expressed by the the Ministries responsible for child welfare and child protection in Armenia. With the Ministry of Education and with the Ministry of Health, the Ministry of Social Security is developing a child welfare strategy, which will feed into the Poverty Reduction Strategy that is currently being drafted by the Armenian Government. The purpose of this Note is to assist the preparation of the child welfare strategy by identifying major issues in family and child welfare, assessing efficiency and effectiveness of current policies and suggesting measures that would better ensure the well-being and future of Armenia's children. This note discusses the dramatic political, economic, and social changes that Armenia went through over the 1990s. Some of them, especially prolonged economic hardship and extensive out-migration have had a criticial impact on child welfare; they have weakened the capacity of Armenia families to manage risks, as well as the ability of the state to provide meaningful support. Other factors contributing to the current state of child welfare include high poverty risk, low health and nutrition status, lesser access to education, effects of migration, and the increased risk of joining an underclass of children deprived of family upbringing. The government will have to focus on a number of key issues in creating an environment ensuring family and child well-being.